Effect of usage on the fatty acid composition and properties of neat palm oil, waste palm oil, and waste palm oil methyl ester - Omojola, Awogbemi; Freddie, Inambao; Emmanuel Idoko, Onuh (International Journal of Engineering and Technology, 2020)
The need to find an environmentally friendly, renewable, and biodegradable fuel to reduce the growing dependence on fossil fuels and its attendant performance and emission inadequacies has increased research in biodiesel. Due to its low cost, availability, and a veritable means of waste disposal, waste vegetable oil from restaurants, waste fats from slaughterhouses, grease from wastewater treatment plants has gained prominence as biodiesel feedstock. This present effort compares the properties and fatty acid (FA) composition of neat palm oil (NPO), waste palm oil (WPO), and waste palm oil methyl ester (WPOME). WPO used to fry fish and chips (WPOFC), and waste palm oil used to fry sausage and chips (WPOSC) were collected at the point of disposal. The WPOFC and WPOSC were converted to WPOMEFC and WPOMESC, respectively, by transesterification and subjected to property determination and gas chromatography-mass spectrometer analysis. The characterization showed that the ratio of saturated FA to unsaturated FA changed from 19.64 %:80.36 % for NPO, to 37.67 %:62.33 % for WPOFC, 54.75 %:45.25 % for WPOSC, 30.43 %:69.58 % for WPOMEFC and 16.2 %:83.8 % for WPOMESC. These outcomes can be attributed to the effect of repeated heating and cooling during frying, contamination from moisture, food fried, and the transesterification reaction.Â Â